The role of eye camps in rural areas of Nepal - Gurung, J.; Tuladhar, S.; Sharma, A (Journal of Gandaki Medical College-Nepal, 2019)
Objective: To evaluate the role of eye camp in reducing avoidable blindness in Nepal. Methods: A cross sectional camp-based study was conducted in a remote village of Eastern Nepal, where a six days eye screening and free surgical camp was done. Results: A total of 467 people were screened, where 280 (60%) were males and 187 (40%) females. Mean age of the patient was 47.6 years. Age related cataract 165 (17.7%) was the commonest cause of decreased vision followed by refractive error 105 (11.2%). Among 165 cataract patients, 81 (49.1%) underwent cataract surgery. The mean age of the operated patient was 74.9 years. Among the operated eyes, visual impairment was present in 56 (69.1%) eyes and blindness in 25 (30.9%). After cataract surgery, visual acuity was restored to 6/6-6/18 in 58 (71.6%), 6/24-6/60 in 18 (22.2%) and five (6.2%) had visual acuity of <6/60. The causes of poor visual acuity in these patients were corneal edema (three cases), anterior uveitis (1 case) and optic atrophy (1 case). Pterygium excision (seven cases), entropion correction (two cases), chalazion I&C (one case) were other surgery performed in the camp. Refractive error was corrected by prescribing glasses. Conclusion: Cataract was found to be the major cause of blindness followed by refractive error. Conducting eye screening and surgical camps helps in restoring vision to the residents of remote areas, thus reducing the burden of blindness due to cataract and refractive error.